Problémás magánjogi elemek a helyi rendeletalkotásban - Árva, Zsuzsanna; Szabó, Judit (Debreceni Jogi Műhely, 2018)
Local governments may establish legal relationships governed by civil law in numerous ways, for example, through the creation of associations, various institutional agreements or they can also do so by means of enacting regulations. In line with the stipulations of the Fundamental Law of Hungary, local governments may adopt regulations on two legal bases: if authorized by law or if they want to regulate a local public affair; however, the regulation may not contradict any higher form of legislation. While in the first case it is not only the right but also the obligation of local governments to enact regulations that can even be sanctioned, in the second case it is almost completely optional. The scope of public affairs regulated by local governments is rather broad. While the smaller local governments typically limit their activities to the regulation of the most urgent matters, the larger local governments enact regulations in a wide range of issues also due to the volume of their responsibilities. In many instances a part of these regulations does not remain within the framework of supremacy but also includes numerous elements of civil law. These could include matters related to parking or municipal housing, as well as problems in connection with public services. Norms regulating peaceful public coexistence represent a separate subject area as in many cases they wish to regulate legal relationships pertaining to privacy. In the case of the latter issue, the clause stating that the local regulations shall not contradict any higher form of law is especially central, as it necessitates the extensive knowledge of civil and in some cases even constitutional law to ensure that such a regulation is enacted that fully complies with the laws.This paper introduces and examines those local government regulations that include elements of civil law also and which typically cause problems, with special emphasis on the rules of peaceful public coexistence. Some of these problems are revealed within the scope of legal supervision practiced over local governments, while in other cases the body reviewing the regulation acts in response to citizens’ initiatives.